DZIKIR CAN REDUCE LABOR PAIN LEVEL - Ai Nur Zannah (International Islamic Medicine Forum, 2021)
Labor pain is a physiological condition that began at the first stage of labor (laten and active phase). Pain comes from uterine contractions and cervical dilation in an attempt to pave the way for birth and encourage babies to be born. Experts find pharmacological and non-pharmacological ways to reduce pain in labor, one of them is Dzikir guided by childbirth helper (midwife). The purpose of this study was to analyze the differences of labor pain level on mother in latent phase before and after applying Dzikir. Subjects were 15 accidentally selected mothers in labor latent phase on March - April in PMB “S” Puger Jember. The design of this study uses a quasi-experimental one group pre-posttest. Results showed significant decreased pain level of mothers after doing Dzikir significantly (Z=-3,578, p≤0.001). In conclusions, there are differences of labor pain level on mother in latent phase before and after applying Dzikir.